2000
DOI: 10.1111/j.1469-185x.2000.tb00056.x
|View full text |Cite
|
Sign up to set email alerts
|

The functional significance of silk decorations of orb‐web spiders: a critical review of the empirical evidence

Abstract: ~ A number of taxonomically diverse species of araneoid spiders adorn their orb-webs with conspicuous silk structures, called decorations or stabilimenta. The function of these decorations remains controversial and -several explanations have been suggested. These include: (1) stabilising and strengthening the web; (2) hiding and concealing the spider from predators; (3) preventing web damage by larger animals, such as birds; (4) increasing foraging success; or (5) providing a sunshield. Additionally, they may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
176
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(182 citation statements)
references
References 53 publications
2
176
1
3
Order By: Relevance
“…For instance, two studies using Argiope aurantia found that the presence of web decoration could either increase prey capture by more than 40% ( Tso 1998) or decrease it by 34% (Blackledge & Wenzel 1999). It seems probable that decoration has evolved to serve many purposes among different lineages of spiders (Herberstein et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, two studies using Argiope aurantia found that the presence of web decoration could either increase prey capture by more than 40% ( Tso 1998) or decrease it by 34% (Blackledge & Wenzel 1999). It seems probable that decoration has evolved to serve many purposes among different lineages of spiders (Herberstein et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly tested explanations for silk decoration function are prey attraction (through signals communicated in the UV spectrum), predator avoidance or 'advertising' the web to warn away large vertebrates from accidentally damaging the web (Herberstein et al 2000;Li 2005;Bruce 2006). Conflicting results ( Tso 1998;Blackledge & Wenzel 1999) have meant that no clear consensus exists yet.…”
Section: Introductionmentioning
confidence: 99%
“…The visibility of orb webs influences how effectively insects avoid webs and potentially their impact energy. The degree to which silk is visually attractive or repulsive to insects is remarkably controversial (see reviews in Herberstein et al 2000;Blackledge et al 2011). However, many features that improve stopping and retention potentials of webs, such as thicker, more tightly packed silk threads and larger glue droplets, clearly enhance web visibility, thereby potentially reducing the webs' interception of insects (Table 1).…”
Section: Orb Websmentioning
confidence: 99%
“…Dessa forma, os dados abundantes na literatura citada acima não devem ser considerados como boas estimativas do comportamento de orbitelas em geral. Dados e generalizações com orbitelas de fios cribelados estão presentes em menor quantidade na literatura (Eberhard, 1971;Herberstein et al 2000;Köhler & Vollrath, 1995;Opell, 1998a;Uetz et al, 1999), e muitas vezes não são distinguidos de considerações gerais acerca do forrageamento de orbitelas.…”
Section: Considerações Finaisunclassified
“…3) Craig e colaboradores (1994) demonstram que a baixa reflexão de UV é derivada na filogenia de Araneoidea e explica a maior diversidade através da menor visibilidade da teia para as presas; entretanto trabalhos da própria autora, entre outros, apresentam a reflexão de UV como uma característica atrativa para insetos (Craig & Ebert, 1994;Li, et al 2004;Watanabe, 1999), ou como uma defesa contra predadores (Bruce et al, 2005;Craig & Freeman, 1991;Zschokke, 2002), entre outras funções (Herberstein, et al, 2000). Além disso, a distribuição dos tipos de reflexão de UV na filogenia pode ser reflexo da ocupação de diferentes nichos ao longo da evolução.…”
Section: Introductionunclassified